Estimating the Meridional Extent of Adiabatic Mixing in the Stratosphere Using Age‐Of‐Air. Issue 4 (13th February 2023) - Gupta, Aman; Linz, Marianna; Curbelo, Jezabel; Pauluis, Olivier; Gerber, Edwin P.; Kinnison, Douglas E.
Abstract: Wave‐induced adiabatic mixing in the winter midlatitudes is one of the key processes impacting stratospheric transport. Understanding its strength and structure is vital to understanding the distribution of trace gases and their modulation under a changing climate. Age‐of‐air is often used to understand stratospheric transport, and this study proposes refinements to the vertical age gradient theory of Linz et al. (2021), https://doi.org/10.1029/2021JD035199 . The theory assumes exchange of air between a well‐mixed tropics and a well‐mixed extratropics, separated by a transport barrier, quantifying the adiabatic mixing flux across the interface using age‐based measures. These assumptions are re‐evaluated and a refined framework that includes the effects of meridional tracer gradients is established to quantify the mixing flux. This is achieved, in part, by computing a circulation streamfunction in age‐potential temperature coordinates to generate a complete distribution of parcel ages being mixed in the midlatitudes. The streamfunction quantifies the "true" age of parcels mixed between the tropics and the extratropics. Applying the revised theory to an idealized and a comprehensive climate model reveals that ignoring the meridional gradients in age leads to an underestimation of the wave‐driven mixing flux. Stronger, and qualitatively similar fluxes are obtained in both models, especially in the lower‐to‐middle stratosphere. While the meridional span of adiabatic mixing in the two models exhibits some differences, they show that the deep tropical pipe, that is, latitudes equatorward of 15° barely mix with older midlatitude air. The novel age‐potential temperature circulation can be used to quantify additional aspects of stratospheric transport. Plain Language Summary: The chemical composition of the stratosphere, that is, the distribution of trace gases like ozone, water vapor, and ozone destroying substances (ODSs), is heavily influenced by the dynamical processes in the region. One such process, quasi‐horizontal mixing, which is driven by planetary waves, rapidly mixes stratospheric trace gases over planetary scales. It is known that the higher the mixing, the longer the trace gases reside in the stratosphere, providing ODS more time to destroy the ozone. However, the properties of this mixing, for instance, its vertical structure, its strength, and how it changes in a changing climate are not fully understood. Past studies have developed a theoretical framework to quantify the mixing strength, that is, how much mass it moves around on average, using simple measures derived from satellite observations of trace gases. This study provides an update to the theoretical framework. The update can lead to a more accurate estimation of the mixing strength. This is done by introducing a new technique called the Γ–θ circulation, which provides a detailed assessment of the mixing, also allowing us to understand its latitudinal variation. The robustness of the revised theory is tested using two climate models with different complexity. Key Points: The isentropic formulation of the leaky pipe stratospheric transport model (Linz et al.,  2021, https://doi.org/10.1029/2021JD035199) is used to estimate midlatitude mixing fluxes A new metric, which quantifies the meridional range of air parcels being mixed across transport barriers, is proposed to estimate mixing The deep tropical stratosphere mixes with the extratropics in the upper stratosphere, but is otherwise remarkably isolated